Design Molecular Imprinting Polymer Coupled with Spectrophotometric Detection for the Determination of Tramadol Hydrochloride in Pure and Pharmaceutical Formulations - Huda Hussein Ali; Yehya Kamal Al-Bayati (Journal of Engineering)
This research describes a new method for estimating tramadol hydrochloride in pharmaceutical formulations using Molecularly Imprinted Solid-Phase Extraction (MISPE) as a sample extraction technique. Acrylamide was used as the functional monomer, trimethylolpropane Trimethacrylate as the cross-linker, and tramadol hydrochloride as the template molecule to make Molecularly Imprinted Polymer (MIP). The new molecularly imprinted polymer was characterized using UV-Vis spectroscopy, Fourier transform infrared spectroscopy, and a scanning electron microscope. The adsorption isotherm of the prepared polymer was determined under the optimum conditions using spectrophotometry at a wavelength of 272 nm. The method's linear dynamic range was found to be 5–140 µg/mL, and the limits of detection (LOD) and quantification (LOQ) were 0.62 and 1.87 µg/mL, respectively. Relative Standard Deviation (RSD%) was less than 2% five times in intra-day and inter-day. This method was successfully utilized to determine tramadol hydrochloride in pharmaceutical formulations with recoveries in the 93.04–104.3% range.